An assessment method of ecosystem services based on stakeholders perceptions: The Rapid Ecosystem Services Participatory Appraisal (RESPA) - Rey Valette, H.; Mathé, S.; Salles, J.M. (Elsevier, 2017)
Using a classification of existing approaches in environment economics and ecological economics, this article presents a method of valuing ecosystem services based on perception surveys. It assesses, on one hand, the level of familiarity with services among a diverse array of stakeholders, citizens and/or service users- and, on the other hand, appraises the relative importance of all the services pertaining to a defined geographical area using two indicators, citation frequency and hierarchical ranking of services selected. In accordance with pragmatist principles, the relative nature of the approach is designed to improve the quality of the assessment. The incentive role of information is given priority to identify learning and communication measures that encourage pro-environmental behaviour and voluntary, individual and collective measures in favour of ecosystem service conservation. The protocol proposed also enables additional information to be collected, especially on the rationale behind choices or the level of familiarity with services. An illustration provided by a case study attests to the pertinence and efficiency of the method which can be used as a tool for decision-making support at regional levels and assisting governance and the enhancement of ecosystem heritage.